2019
DOI: 10.1177/0959683618824761
|View full text |Cite
|
Sign up to set email alerts
|

A multi-model analysis of ‘Little Ice Age’ climate over China

Abstract: Using the numerical experiments undertaken by nine climate models within the framework of the Paleoclimate Modeling Intercomparison Project Phase 3 (PMIP3), the ensemble simulations with the Community Earth System Model for the last millennium (CESM-LME), and proxy data, we investigate the climate over China during the ‘Little Ice Age’ (LIA; from 1450 to 1850 CE) against the background of the last millennium (from 850 to 1850 CE). The surface air temperature averaged over China generally decreased over time du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 96 publications
1
9
0
Order By: Relevance
“…Overall, the simulated SATs in all regions exhibit relative cooling characteristics, similar to the reconstruction (except for the TP region). Although different simulated archives have different responses to external forcings (Zhou et al ., 2019), the SAT across the northern China region is more sensitive in the LIA than the NH, which is also consistent with the reconstruction.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Overall, the simulated SATs in all regions exhibit relative cooling characteristics, similar to the reconstruction (except for the TP region). Although different simulated archives have different responses to external forcings (Zhou et al ., 2019), the SAT across the northern China region is more sensitive in the LIA than the NH, which is also consistent with the reconstruction.…”
Section: Resultssupporting
confidence: 85%
“…All individual simulations show warmer temperatures in the MCA and cooler in the LIA (Figure 4, with reference to the period of 1401–1850 AD), consistent with that of the reconstruction. The results agreed with previous studies based on the model simulations, which showed warmth conditions in the peak MCA (Yan et al ., 2015) and cold conditions in the LIA (Zhou et al ., 2019) over the whole of China. However, the performance differences are more remarkable for the simulations than the reconstruction over the MCA (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the models involved in the paleoclimate modelling intercomparing project 3 (PMIP3), HadCM3 (Hadley Centre Coupled Model version 3) has better simulation ability towards the trend of extreme precipitation change and the spatial pattern of precipitation in China (Chen et al 2014), and well captures the PDO, El Niño and IOD climatic modes (Zhou et al 2019;Kay and Washington 2008). Here we used a 1200-years long control run of HadCM3 2°×2° simulation, which indicated that the external forcing are keeping constant, of which, the concentrations of greenhouse gases and aerosols are kept the level of preindustrial era, and the detected extreme precipitation changes may be only attributed to internal variability (Collins et al 2001).…”
Section: Data Source and Methodsmentioning
confidence: 99%
“…The last millennium (AD 850-1850) provides an opportunity to examine the role of natural forcings (i.e. solar activity and volcanic eruptions) in Asian climate change (Jones et al, 1998;Schmidt et al, 2011;Shi et al, 2015;Zhou et al, 2019). There are two typical intervals over the last millennium: the Variation of the summer Asian westerly jet over the last millennium based on the PMIP3 simulations Nanxuan Jiang, 1,2,3 Qing Yan 1,4,5 and Huijun Wang 1,5 Abstract Investigation of the evolution of summer Asian westerly jet (AWJ) in Earth history may deepen our understanding of the behavior of AWJ in the present and future.…”
Section: Introductionmentioning
confidence: 99%